"Between a Regular Person and a Brand": Managing the Contradictions of the Authentic Self-Brand. Issue 1 (2nd January 2021) - Whitmer, Jennifer M.
ABSTRACT: Drawing on qualitative research on personal style blogging, I examine how the marketization of self through the process of self-branding impacts self-presentation, particularly the performance of authenticity. My research suggests that one of the challenges to performing authenticity is due to the contradiction between the qualities associated with authenticity and the work which goes into performing a self which appears worthy of visibility. This research complicates analyses of branding which focus on authenticity as the source of branded value, while also elucidating the mechanisms by which performing branded selves impacts self-presentation.